The neuroprotective potential of phytochemicals in traumatic brain injury: mechanistic insights and pharmacological implications - Hasan, Gulam Mustafa; Anwar, Saleha; Shamsi, Anas; Sohal, Sukhwinder Singh; Hassan, Md. Imtaiyaz (Frontiers in Pharmacology, 2024)
Traumatic brain injury (TBI) leads to brain damage, comprising both immediate primary damage and a subsequent cascade of secondary injury mechanisms. The primary injury results in localized brain damage, while the secondary damage initiates inflammatory responses, followed by the disruption of the blood-brain barrier, infiltration of peripheral blood cells, brain edema, and the release of various immune mediators, including chemotactic factors and interleukins. TBI disrupts molecular signaling, cell structures, and functions. In addition to physical tissue damage, such as axonal injuries, contusions, and hemorrhages, TBI more broadly interferes with brain functioning, impacting cognition, decision-making, memory, attention, and speech capabilities. Despite a deep understanding of the pathophysiology of TBI, an intensive effort to evaluate the underlying mechanisms with effective therapeutic interventions is imperative to manage the repercussions of TBI. Studies have commenced to explore the potential of employing natural compounds as therapeutic interventions for TBI. These compounds are characterized by their low toxicity and limited interactions with conventional drugs. Moreover, many natural compounds demonstrate the capacity to target various aspects of the secondary injury process. While our understanding of the pathophysiology of TBI, there is an urgent need for effective therapeutic interventions to mitigate its consequences. Here, we aimed to summarize the mechanism of action and the role of phytochemicals against TBI progression. This review discusses the therapeutic implications of various phytonutrients and addresses primary and secondary consequences of TBI. In addition, we highlighted the roles of emerging phytochemicals as promising candidates for therapeutic intervention of TBI. The review highlights the neuroprotective roles of phytochemicals against TBI and the mechanistic approach. Furthermore, our efforts focused on the underlying mechanisms, providing a better understanding of the therapeutic potential of phytochemicals in TBI therapeutics.